2009
DOI: 10.1038/ki.2009.343
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean diets are associated with a lower incidence of metabolic syndrome one year following renal transplantation

Abstract: Considering the high prevalence of metabolic syndrome and its association with cardiovascular mortality, we prospectively evaluated the role of diet in the incidence of metabolic syndrome in renal transplant recipients. Our prospective cohort of 160 adult renal allograft recipients was followed for 1 year and had no existing metabolic syndrome or diabetes mellitus. Routine dietary intakes were assessed with food-frequency questionnaires, and metabolic syndrome was defined according to the Adult Treatment Panel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 38 publications
2
24
0
1
Order By: Relevance
“…In line with our results on NODAT another study showed an association between adherence to a Mediterranean Style diet and a lower incidence of metabolic syndrome after transplantation 32. Prospective cohort studies among patients with cardiovascular disease showed that a Mediterranean Style diet was associated with a lower risk of all-cause mortality 33–35.…”
Section: Discussionsupporting
confidence: 87%
“…In line with our results on NODAT another study showed an association between adherence to a Mediterranean Style diet and a lower incidence of metabolic syndrome after transplantation 32. Prospective cohort studies among patients with cardiovascular disease showed that a Mediterranean Style diet was associated with a lower risk of all-cause mortality 33–35.…”
Section: Discussionsupporting
confidence: 87%
“…However, there were no differences in all-cause mortality between the DASH versus control diets [ 76 ]. The Mediterranean diet has also been associated with lower risk of metabolic syndrome after kidney transplantation [ 77 ]. With respect to kidney disease outcomes, a 15-year observational study demonstrated that adherence to the Mediterranean diet was associated with lower risk of rapid decline in eGFR [ 78 ].…”
Section: Comparison Of Prescribed Dietsmentioning
confidence: 99%
“…Another recent study using food frequency questionnaires in 160 kidney transplant recipients indicated that a Mediterranean dietary pattern is associated with a reduced risk of metabolic syndrome in these patients (56). The long‐term outcomes of such a diet were not examined in this study and the relevance of these findings to MHD patients is questionable.…”
Section: Consequences Of Qualitative Deficiencies In Nutritional Intakementioning
confidence: 99%